PERAN KEPERCAYAAN MAHASISWA TERHADAP DOSEN DI LINGKUNGAN PERGURUAN TINGGI MAKASSAR - Piara, Muhrajan; Hidayat, Muhammad Nur (STIT Al-Ittihadiyah Labuhanbatu Utara, 2023)
Abstract: This study aimed to explore trust of collage students in Makassar towards their lecturers. There were 238 research participants, consisted of 128 females and 110 males. The data collection technique applied a questionnaire. After collectig data, we analyzed through simple regression analysis in SPSS application. The result of this study showed that 68% of trust is formed by personal and relational attributes. The aspects which were not significant to this trust model are closeness and reciprocity. Further research also found that 33% of students felt that their lecturers met the desired criteria while 67% of students felt that their lecturers did not meet the desired criteria. In the end, this study provided an overview of the appropriate model of trust between students towards lecturers in the higher education environment in general and specifically in the university environment in Makassar. The author hoped that this study will become a reference in building a conducive academic evironment and initial step to support an effective teaching and learning process, as well as an effort to avoid conflicts that occur in power relations between lecturers and students.